Mentoring and Entrepreneurship in Higher Education: A Study from the Plithogenic Statistics - Wilmer Ortega Chávez; Janett Karina Vásquez Pérez; Beker Maraza Vilcanqui; Nazario Aguirre Baique; Carlos Manuel Sacarías Mercado; Ciro Angel Lazo Salcedo; Reyna Olano del Castillo (Neutrosophic Sets and Systems)
Entrepreneurship management in university students is a key factor for economic and social development, especially in intercultural contexts such as the Peruvian Amazon. However, the absence of effective training strategies limits the strengthening of these competencies. This study aims to evaluate the impact of a mentoring program on strengthening entrepreneurship management in students at the National Intercultural University of the Amazon in Peru. The research concludes that the implementation of mentoring programs can represent a key strategy to promote student entrepreneurship in regions with development needs, providing relevant evidence for educational practice and future interventions in higher education. Plithogenic statistics is an extension of traditional statistics that allows the analysis of data sets with multiple levels of uncertainty, contradiction, and neutrality, integrating variables that do not necessarily belong entirely to a sample or population. Its importance lies in the fact that it provides mathematical tools to study complex real-world phenomena—such as social, medical, or organizational dynamics—where the data are not entirely clear or defined, thus improving the accuracy of analysis and decisionmaking. It is for all these advantages that we use the Plithogenic Statistics as a tool for the study to be conducted. Mentoring and entrepreneurship in higher education encompass several dimensions that interact dynamically with each other, and there are also components of uncertainty within this phenomenon.